Air-processed stable near-infrared Si-based perovskite light-emitting devices with efficiency exceeding 7.5%. Issue 4 (24th December 2021) - Xu, Xiaoxiao; Xiao, Ke; Hou, Guozhi; Zhu, Yu; Zhu, Ting; Xu, Ling; Xu, Jun; Chen, Kunji
Abstract : Two composite layers are used to enhance the efficiency of Si-based near-infrared perovskite light-emitting devices, which are produced in ambient air, and the external quantum efficiency increased to 7.5%. Abstract : Organic perovskite materials have attracted considerable attention because of their potential applications in various types of opto-electronic devices. Nowadays, obtaining high-performance devices fabricated in ambient atmosphere is a challenge. In this study, we report Si-based near-infrared (NIR) perovskite light-emitting devices (PeLEDs) with enhanced efficiency by an air-processed technique with two composite layers. One layer is constructed using 4, 4′-bis(N-carbazolyl)-1, 1′-biphenyl (CBP) with poly-TPD coating as a hole transport layer (HTL) to balance carrier injection, and the other is constructed doping poly(methyl methacrylate) (PMMA) with antisolvent to passivate defects and protect MAPbI3 from degradation by water and oxygen. Through these two composite layers, the EL performance is enhanced with an external quantum efficiency (EQE) of 7.5%, and the stability is also improved to 200 min after the introduction of another m-PMMA layer. Our results provide a simple way to manufacture high-efficiency and stable PeLEDs under air condition.